A systematic review of key success factors in postgraduate studies - Nwosu, L. I.; Segotso, T.; Enebe, N. B.; Nyakuwanika, M. (South African Journal of Higher Education, 2024)
Background: Massification of higher education and growth in undergraduate students has propelled a wave of students seeking advanced degrees. Increasing numbers of postgraduate students reflect the performance of Higher Education Institutions (HEIs) and highlight the need to study key elements affecting postgraduate academic success. Purpose: This systematic literature review (SLR) aims to identify key success factors related to postgraduate studies. Research approach: The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines were used to guide the reporting of this review. Articles in ScienceDirect, Jestp.com, Ed.gv, Tandfonline.com, Oup.com, Springer.com, Researchgate.net, Sagepub.com, Wiley.com, Alt.ac.uk, and Stor.org were searched between January 2013 and January 2023. Results: A final 28 studies from 14 countries were reviewed to provide a holistic assessment of major factors affecting postgraduate academic success. The most common success factors in postgraduate studies are teaching and learning methods, quality research supervision, research capacity building, library services, Postgraduate Student Office workshops, and student characteristics. Limitations within some factors were also reported. Conclusion and implication: The study concluded that postgraduate students’ ability to function effectively depends on adequately implementing and managing critical and complex factors. The results of the study will inform postgraduate programme practitioners.